Pre-exenterative chemotherapy, a novel therapeutic approach for patients with persistent or recurrent cervical cancer - Uribe Jesus; Chanona Jose; Cantu David; Gonzalez Aaron; Cetina Lucely; Dolores Rigoberto; Lopez-Graniel Carlos; Candelaria Myrna; Brom Rocio; de la Garza Jaime; Duenas-Gonzalez Alfonso (BMC Cancer, 2005)
Abstract Background Most cervical cancer patients with pelvic recurrent or persistent disease are not candidates for exenteration, therefore, they only receive palliative chemotherapy. Here we report the results of a novel treatment modality for these patients pre-exenterative chemotherapy- under the rational that the shrinking of the pelvic tumor would allow its resection. Methods Patients with recurrent or persistent disease and no evidence of systemic disease, considered not be candidates for pelvic exenteration because of the extent of pelvic tumor, received 3-courses of platinum-based chemotherapy. Response was evaluated by CT scan and bimanual pelvic examination; however the decision to perform exenteration relied on the physical findings. Toxicity to chemotherapy was evaluated with standard criteria. Survival was analyzed with the Kaplan-Meier method. Results Seventeen patients were studied. The median number of chemotherapy courses was 4. There were 9 patients who responded to chemotherapy, evaluated by bimanual examination and underwent pelvic exenteration. Four of them had pathological complete response. Eight patients did not respond and were not subjected to surgery. One patient died due to exenteration complications. At a median follow-up of 11 months, the median survival for the whole group was 11 months, 3 months in the non-operated and 32 months in those subjected to exenteration. Conclusion Pre-exenterative chemotherapy is an alternative for cervical cancer patients that are no candidates for exenteration because of the extent of the pelvic disease. Its place in the management of recurrent disease needs to be investigated in randomized studies, however, its value for offering long-term survival in some of these patients with no other option than palliative care must be stressed.